Comparative economics of maize grain and seed production in Okhaldhunga, Nepal - Dulal, P. R.; Marahatta, S. (Journal of Agriculture and Forestry University, 2020)
Maize (Zea mays L.) cultivation is very popular in Nepal. Basically, in the rural hills of Nepal such as Okhaldhunga, it dominates any other crop production. This study was done to for a comparative assessment of economics, marketing, and to identify major problems of maize seed and grain production in hilly eastern district of Okhaldhunga during June of 2017. The data were obtained by the interview of 66 purposively selected producers (33 each of maize grain and seed producers) with the use of pre-tested semi-structured questionnaire. Both the grain and seed producers were similar in terms of socio-demographic characteristics and marketing accessibilities, but the seed producers were significantly benefited from the trainings, extension services, and credit facilities despite having comparatively small size of land holding (0.14 ha) than the grain producers. The inputs (manures, fertilizers, and the seed) contributed 48% and 50% of the total cost incurred for grain and seed production, respectively whereas the pre-sowing and sowing activities contributed more than 77% of cost in both the cases. In spite of higher cost for seed production, the benefit cost ratio of seed production was higher (1.52) than grain production (1.13). Findings also revealed that only 24% of the total harvest was processed and marketed as seed whereas using optimum quantity (66% middle portion of the cob) for seed production could further increase the income by 23.35%. The major production problems were scarce farm labor followed by lack of infrastructures, while low seasonal price followed by low volume of production ranked the first and second most important marketing related problems. Subsidies on the agri-inputs, timely availability of inputs, and encouragement of the youth towards agri-enterprise via various youth oriented programs can be done to overcome these problems.